Higher Education Fund (HEF) Students Resources mobilization in higher education - Kithuri, Fr. Dr. Kinoti E.; Thuranira, Prof. Simon (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The demand for University education in Kenya has risen over the last few years. This has been driven by the growth in the knowledge-based economy and demographic changes and needs. Kenya has demography that has more youth comprising over 60% of the total population. Most of the youth seek University education and therefore it becomes increasingly important to ensure that higher education systems are adequately funded to increase their overall capacity, quality and equity. This paper analyzed financing Tertiary education in Kenya with specific attention to the new public university funding model unveiled by the Kenya Kwanza government in 2023. Methods, utilized are that of a secondary data method literature review and policy analysis. The study makes recommendations on a viable financing framework for University education and research. Kenya’s models have metamorphosed over years, 1990s The Kenya Government was financing the entire University education, including giving students’ stipends. The Kamunge Report of 1988 entitled; introduced cost-sharing where the Government was to pay Ksh. 70,000 for every student admitted to University, while the parents or guardians were to pay Ksh. 16,000 as tuition fees. The students received Ksh. 50,000 from Higher Education Loan Board (HELB) as loans for their upkeep, accommodation and book allowance (HELB, 2023) The government grant per student also increased over time to a high of Ksh. 242,000 per student by 2016, with disparities within Universities. The direct tuition fees component paid by students, however, remained the same, although households continued to meet other associated costs. In FY 2017/2018 Government introduced Differentiated Unit Cost (DUC) as a model for funding public Universities. DUC is based on a number of parameters, including staff cost, student-staff ratio, student numbers, cost of infrastructure and operations, student load and cost of programs (MDUC Report, 2015). Fourteen clusters were approved by the Universities Fund, with programmes being funded at negotiated Maximum Differentiated Unit Cost (MDUC). Clinical medicine and dentistry have the highest DUC of Ksh. 720,000, while Applied Humanities and Social Sciences have the lowest cost of Ksh. 180,000. This funding model has been in place till this year (HELB, 2023). New model Proposed by The New Higher Education Funding Model, unveiled by President William Ruto on May 3, 2023, aimed to address challenges encountered by public universities and Technical and Vocational Education (TVET) institutions due to massive enrollment and inadequate funding. The framework replaces the Differentiated Unit Cost (DUC) prioritizing a student’s financial need and separates placement from funding. Under this model, universities and TVET institutions will no longer receive block funding in the form of capitation. Instead, funding for students will be provided through scholarships, loans, and household contributions. Following the introduction of the new model, students will have access to scholarships and loans to finance their higher education. Students must apply individually for the loans and scholarships, and the applications assessed through Means Testing Instrument (MTI). The MTI determines the student’s level of financial need Based on students categorized as vulnerable, extremely needy, needy, or less needy. Conclusion the funding method has great potential if and when well utilized, especially reaching out on families and students who have been left out of high education because social economic characters of poverty, no parents, and support system. However, no scientific method determines a student’s level of neediness, raising concerns that students requiring scholarships and loans might not be appropriately classified for awards. Additionally, the distribution of funds lacks transparency. Details such as loan terms, interest rates, repayment conditions, and the process for appealing declined scholarship requests are not disclosed. Furthermore, the funding model excludes students under 18.The study recommends a longitudinal study that Progressive can follow funding HEF for some years step wise eligibility follow up of students applying and actual financial reception and payment in order to strongly argue for or against expected outcomes Ensures that all eligible Kenyan students receive adequate financial support for their education, Promotes the provision and access to quality higher education, Ensures that all students are equitably and adequately supported based on their level of financial need, Ensures timely disbursement of funds to students through their higher education institutions. These outcomes are yet to show as indicators in a student’s life t being a less than 2 years old model being budget in progress.